MSAA DAN MRNIA BAGI RECOVERY DANA BLBI: SEBUAH JALAN KELUAR ATAU â€œJALAN UNTUK KELUARâ€ - Tri Widya Kurniasari (LIPI Press, 2006)
In performing its task to recovery, BPPN has an authority to manage assets guaranteed by debtors who have got BLBI after the monetery crisis in 1997. BPPN also has an authority to sell assets of debtors who have signed Master Settlement and Acquitition Agreement (MSAA) or Master Refinancing and Note Issuance Agreement (MRNIA). Both are the instruments, offered by BPPN as a recovery procedure. The assets can be sold directly by either BPPN or its representatives. Generally speaking, BPPN creates a holding company to manage the selling of assets of each organization group, who have signed the MSAA/MRNIA. However, many debtors of BLBI use these instruments as a way to escape their responsibility to return BLBI. This is caused by, among others, release and discharge clausuls in those agreement. It indicates that there is still the weaknesses in those agreement. Therefore, it must reviewed to make its clear. This article attempts to analyze those agreement, not only their status in the public and private law in this country but also the advantaged value of those agreement in the economic sector. In fact, those agreement can be the out of court settlement in the private law only but canâ€™t abolish the demand in the public law. Keywords: MSAA, MRNIA, Dana BLBI, BPPN